Epidemiology of colorectal cancer: incidence, mortality, survival, and risk factors - Prashanth Rawla; Tagore Sunkara; Adam Barsouk (Gastroenterology Review)
According to GLOBOCAN 2018 data, colorectal cancer (CRC) is the third most deadly and fourth most commonly diagnosed cancer in the world. Nearly 2 million new cases and about 1 million deaths are expected in 2018. CRC incidence has been steadily rising worldwide, especially in developing countries that are adopting the “western” way of life. Obesity, sedentary lifestyle, red meat consumption, alcohol, and tobacco are considered the driving factors behind the growth of CRC. However, recent advances in early detection screenings and treatment options have reduced CRC mortality in developed nations, even in the face of growing incidence. Genetic testing and better family history documentation can enable those with a hereditary predisposition for the neoplasm to take preventive measures. Meanwhile, the general population can reduce their risk by lowering their red meat, alcohol, and tobacco consumption and raising their consumption of fibre, wholesome foods, and certain vitamins and minerals.